The Effect of Homerton Covid Psychological Support (HCPS) in Overcoming Mental Health Problems in Covid-19 Health Workers - Latifah, Riza Arisanty; Annisa, Rully (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Coronavirus Disease-19 (COVID-19) is an infectious disease that not only attacks patients, virus also attacks several health workers who often have direct contact with positive COVID-19 patients. RSD Gunung Jati is a government hospital that accepts and treats COVID-19 patients. This causes concern both for the health workers themselves and for other health workers who have worked in the same place. So that many health workers will experience problems, such as anxiety, stress, fatigue, fear and even insomnia. Mental health services in the UK have issued guidelines for meeting mental health needs, namely through Homerton Covid Psychological Support (HCPS). HCPS is a guideline designed as mental and psychological health support for COVID-19 health workers. The purpose of this study was to determine the effect of Homerton Covid Psychological Support in reducing mental health problems for COVID-19 health workers at Gunung Jati Hospital, Cirebon. The sample in this study amounted to 32. The design of this study was pre-experimental with one group pretest-posttest, namely this design revealed a causal relationship by involving one group of subjects. This study uses data analysis with statistical tests with the T-Test analysis method. The results of the Paired t-Test showed a p-value = 0.000 in the intervention group. The results of the Paired t-Test concluded that there were significant differences after treatment in the intervention group.